Evaluation of Apoptosis and Autophagy Inducing Potential of Berberis aristata, Azadirachta indica, and Their Synergistic Combinations in Parental and Resistant Human Osteosarcoma Cells - Sengupta, Pracheta; Raman, Sukanya; Chowdhury, Rajdeep; Lohitesh, K.; Saini, Heena; Mukherjee, Sudeshna; Paul, Atish (Frontiers in Oncology, 2017)
Cancer is a multifactorial disease and hence can be effectively overcome by a multi-constituently therapeutic strategy. Medicinal plant extracts represent a perfect example of such stratagem. However, minimal studies have been done till date that portray the effect of extraction techniques on the phyto-constituent profile of plant extracts and its impact on anticancer activity. In the present study, we have evaluated the anticancer potential of methanolic extracts of Berberis aristata root and Azadirachta indica seeds prepared by various extraction techniques in human osteosarcoma (HOS) cells. Soxhlation extract of B. aristata (BAM-SX) and sonication extract of A. indica (AIM-SO) were most effective in inducing apoptosis in parental drug sensitive, as well as resistant cell type developed by repeated drug exposure. Generation of reactive oxygen species and cell cycle arrest preceded caspase-mediated apoptosis in HOS cells. Interestingly, inhibition of autophagy enhanced cell death suggesting the cytoprotective role of autophagy. Combination studies of different methanolic extracts of BAM and AIM were performed, among which, the combination of BAM-SO and AIM-SO (BAAISO) was found to show synergism (IC50 10.27 µg/ml) followed by combination of BAM-MC and AIM-MC (BAAIMC) with respect to other combinations in the ratio of 1:1. BAAISO also showed synergism when it was added to cisplatin-resistant HOS cells (HCR). Chromatographic profiling of BAM-SX and AIM-SO by high performance thin layer chromatography resulted in identification of berberine (Rf 0.55), palmitine (Rf 0.50) in BAM-SX and azadirachtin A (Rf 0.36), azadirachtin B (Rf 0.56), nimbin (Rf 0.80), and nimbolide (Rf 0.43) in AIM-SO. The cytotoxic sensitivity obtained can be attributed to the above compounds. Our results highlight the importance of extraction technique and subsequent mechanism of action of multi-constituential B. aristata and A. indica against both sensitive and drug refractory HOS cells.